Identity in Literature - Holubová, Barbora (Univerzita Pardubice, 2025)
This diploma thesis focuses on the construction of identity in contemporary British literature by analyzing three works: My Beautiful Laundrette by Hanif Kureishi, White Teeth by Zadie Smith, and Hotel World by Ali Smith. The theoretical part defines the concept of identity, presents Erikson's theory of psychosocial development, outlines different types of identity, and describes the development of contemporary British literature, including the significance of multiculturalism. The practical part analyzes the representation of ethnic, sexual, and social identities in the chosen literary works.
Keywords: britská literatura; etnická identita; psychosociální vývoj; sexuální identita; sociální identita; British literature; ethnic identity; psychosocial development; sexual identity; social identity